Study on Identification and Separation of the Antifungal Antibiotic from its Fermentation Broth of Streptomyces hygroscopicus BOS-013 Strain - Yong, Wang; Wei, Zhang; Wen-Ge, Zhang; Ning-Ning, Wang; Dan, Lu; Lin, Zhou; Cong-Yang, Yan (Asian Journal of Chemistry, 2012)
BOS-013 actinomycete strain was obtained by separating difference soil of areas from Chang Bai Mountain. The antifungal antibiotic produced by Streptomyces hygroscopicus BOS-013 was purified by means of macro-porous adsorbent resin and thin-layer chromatography. The separation and purification of the antifungal antibiotic from its fermentation broth of Streptomyces hygroscopicus BOS-013 strain by simulated moving bed chromatography and the crystal of the antibiotic with high purity was obtained. In this paper, the methods of purification by adsorbing of microporous adsorbent resin and detection by high performance liquid chromatography with mass spectrum (HPLC-MS) were established. The study lays a good foundation for its physical-chemical properties. Meanwhile,we identified its structure by spectral analyses. Quasi-molecular ion peak [M + H]+ was 547 given by positive ion mode-electrospray ionization-mass spectrometry and pushed-out its molecular weight was 546. Its molecular formula was C30H43O9. We did not find this compound, so it was infered as a new compound temporarily after Scifinder search.